Estimating the Population Benefits and Costs of Rituximab Therapy in the United States from 1998 to 2013 Using Real-World Data. Issue 4 (April 2016) - Danese, Mark D.; Reyes, Carolina M.; Gleeson, Michelle L.; Halperin, Marc; Skettino, Sandra L.; Mikhael, Joseph
Abstract : Background: Rituximab was approved in 1997 and is regularly one of the largest drug expenditures for Medicare; however, its benefits and costs have not been estimated from a population perspective. Objectives: To estimate both the clinical and the economic outcomes of rituximab for its approved hematological uses at the population level. Research Design: Analyses using cancer registry incidence data from the Surveillance, Epidemiology, and End Results (SEER) program, and outcomes data from SEER data linked with Medicare administrative claims (SEER-Medicare data). These results were incorporated into an epidemiological simulation model of the population over time. Subjects: We modeled all United States patients from 1998 to 2013 diagnosed with diffuse large B-cell lymphoma, follicular lymphoma, or chronic lymphocytic leukemia. Measures: Using this model, we estimated the life-years saved, as well as their economic benefit, in the United States population. We also estimated the incremental cost of adding rituximab to chemotherapy. All economic inputs were based on Medicare reimbursed amounts inflated to 2013 dollars. Results: There were 279, 704 cumulative life-years saved which were valued at 25.44 billion. The incremental direct medical cost of rituximab was estimated to be 8.92 billion, resulting in an incremental economic gain of 16.52 billion. Conclusions: These analyses, based on real-world evidence, show that the introduction of rituximab into clinical practice has produced a substantial number of incremental life-years. Importantly, the economic benefit of the life-years gained greatly exceeds the added costs of treatment. Abstract : Supplemental Digital Content is available in the text.